"The whole wall fell apart, and I felt free for the first time": Men's perceptions of helpful responses during discussion of child sexual abuse. (February 2021) - Easton, Scott D.; Parchment, Tyrone M.
Abstract: Background: There is a growing awareness of the prevalence and consequences of childhood sexual abuse (CSA) for boys. Disclosure experiences often impact long-term functioning following CSA. Current understanding around disclosure has evolved from a singular act of telling to a broader, reciprocal process that can include discussion. However, there is limited empirical evidence about what constitutes a helpful response from others during the discussion of CSA for men. Objective: This study examines the characteristics of a helpful response during the discussion of CSA among a large sample of men with histories of CSA. Participants and setting: Participants included 487 men ranging in age from 19 to 84 years (mean = 50.1) who completed an anonymous, one-time online survey as part of a larger project on men's health and well-being. Participants were recruited through research announcements on web sites and discussion boards of national organizations that support adult survivors of CSA. Methods: Narrative data from an open-ended prompt were analyzed using qualitative content and inductive thematic analyses over eleven months. Results: The analysis yielded five superordinate themes on men's perceptions of helpful responses from others during discussions of CSA: (1) experience; (2) personal characteristics; (3) specific actions; (4) therapeutic interventions; and (5) insights. Conclusions: Clinicians and health care professionals should convey an awareness of CSA for boys, reach out to men dealing with difficulties tied to early trauma, and implement helpful response strategies in discussions of CSA. Family members, friends, and colleagues within men's social networks can also support recovery with helpful response strategies.